Complex high-risk indicated percutaneous coronary interventions (CHIP-PCI) in elderly patients. (3rd October 2022) - Marschall, A; Marti Sanchez, D; Ferreiro, J L; Lopez Palop, R; Ojeda, S; Avanzas, P; Jimenez Mazuecos, J M; Carrillo Saez, P; Gutierez-Barrios, A; Pinar, E; Linares, J A; Diego, A; et al.
Abstract: Introduction: Complex high-risk indicated percutaneous coronary intervention (CHIP-PCI) is a poorly defined concept. A recent large-scale study identified various patient- and procedure-related factors that were associated with in-hospital major adverse cardiac or cerebrovascular events (MACCE), which were used to construct a CHIP-score [1]. Purpose: To investigate the predictive value of patient- and procedure related risk factors, based on the CHIP-score, in a large cohort of elderly patients. Methods: This is a retrospective multicenter study of 20 centers, including patients of ≥75 years of age, that underwent PCI in the period of 2012–2019. The primary endpoint of MACCE was defined as cardiovascular death, myocardial infarction, revascularization or stroke. The follow-up time was 1 year. We created univariate and multivariate Cox regression models in order to investigate the predictive value of the CHIP-score variables (other than age, Table 2). Results: A total of 2724 patients with a mean age of 81 (± 4.3) years were included in the study. Baseline characteristics are depicted in Table 1. The mean CHIP score was 1.74 (± 1.2) and 2262 (83%) had at least one CHIP criteria. At 1-year follow-up, 267 (9.8%) met the primary endpoint. Out of 11 investigated CHIP-score variables, only 5 were independent predictors of 1-year MACCE in adjusted regression models: Prior myocardial infarction (HR 1.56 (95% CI: 1.10–1.90), p=0.009), left ventricular ejection fraction <30% (HR: 2.02 (95% CI: 1.34–3.0, p<0.001), chronic kidney disease (HR 1.55 (95% CI: 1.21–2.02, p<0.001), left main coronary PCI (HR: 2.35 (95% CI: 1.29–4.89, p<0.001) and non-radial access (HR: 1.57 (95% CI: 1.19–1.85, p=0.002). See Table 2 for details. Overall MACCE was 4.5% when CHIP was 0, as compared to 10.7% with any CHIP factor present (p<0.001) (Figure 1). A CHIP of 4+ or higher was present in 246 (9%) patients and was associated with a three-fold increase in 1-year MACCE (HR: 2.9 (95% CI: 2.1–3.9), p<0.001). Conclusions: The CHIP-score retains significant prognostic value in the elderly population. The implication of a CHIP-score might be a future tool for risk stratification in clinical practice, not only for in-hospital MACCE but also on long-term follow-up. In the special population of elderly patients, 3 patient related and 2 procedure related factors showed to be especially helpful for risk assessment. Funding Acknowledgement: Type of funding sources: None.